2018
DOI: 10.5688/ajpe6239
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Portfolios in US Pharmacy Schools

Abstract: Objective. To conduct a review of the pharmacy literature on the use of portfolios in US pharmacy schools.Findings. This study provides examples of how pharmacy schools are using portfolios in various parts and across their curricula, however, assessment/outcome data is lacking. These examples can be used as a starting point for schools as they begin to design their own use of portfolios. Overall, students indicated that the use of portfolios is important in their professional development, but significant time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…The need to expand the scope of a literature search to include additional disciplines in academia was also stated by Green et al [5] Medicine, radiology, midwifery, pharmacy, and dentistry are healthcare disciplines that utilize academic portfolios to track student development and competency attainment. [7][8][9][10][11] A supportive stance for the use of e-portfolios was common with comments such as "an integrative e-Portfolio experience can help students link and make meaning from various learning experiences" [12] and "findings indicated that learning portfolio practice can enhance the nature of the learning experience by providing students with a personal space to evaluate their own learning, to process their thoughts and experience and to document their lives and learning in an authentic and meaningful way". [13] Similar to the skills nurses need to develop, pharmaceutical standards require demonstration of "problem solving, educating different audiences, patient advocacy, interprofessional collaboration, cultural sensitivity, communication, leadership, innovation/entrepreneurship, and professionalism" which Daugherty and Cumberland propose are best suited for expression "via reflective portfolios".…”
Section: Describe Relevant Scholarshipmentioning
confidence: 99%
See 4 more Smart Citations
“…The need to expand the scope of a literature search to include additional disciplines in academia was also stated by Green et al [5] Medicine, radiology, midwifery, pharmacy, and dentistry are healthcare disciplines that utilize academic portfolios to track student development and competency attainment. [7][8][9][10][11] A supportive stance for the use of e-portfolios was common with comments such as "an integrative e-Portfolio experience can help students link and make meaning from various learning experiences" [12] and "findings indicated that learning portfolio practice can enhance the nature of the learning experience by providing students with a personal space to evaluate their own learning, to process their thoughts and experience and to document their lives and learning in an authentic and meaningful way". [13] Similar to the skills nurses need to develop, pharmaceutical standards require demonstration of "problem solving, educating different audiences, patient advocacy, interprofessional collaboration, cultural sensitivity, communication, leadership, innovation/entrepreneurship, and professionalism" which Daugherty and Cumberland propose are best suited for expression "via reflective portfolios".…”
Section: Describe Relevant Scholarshipmentioning
confidence: 99%
“…[13] Similar to the skills nurses need to develop, pharmaceutical standards require demonstration of "problem solving, educating different audiences, patient advocacy, interprofessional collaboration, cultural sensitivity, communication, leadership, innovation/entrepreneurship, and professionalism" which Daugherty and Cumberland propose are best suited for expression "via reflective portfolios". [11] 1.3.1 Benefits of academic portfolios Bhargava et al [7] spoke to an increased utilization of portfolios in both academic and employment settings. Gadbury-Amyot et al [9] saw a positive correlation between student portfolio quality and grade point average among dental hygiene students.…”
Section: Describe Relevant Scholarshipmentioning
confidence: 99%
See 3 more Smart Citations